2002
DOI: 10.1161/hq0302.105593
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 Receptor Antagonism Reduces Monocytic Foam Cells in Mice

Abstract: Abstract-Leukotriene B4 (LTB4) is a potent chemotactic agent that activates monocytes through the LTB4 receptor (BLTR). We tested the hypothesis that LTB4 receptor blockade would slow atherosclerotic progression by inhibiting monocyte recruitment. Homozygous low-density receptor knockout (LDLr Ϫ/Ϫ ) mice and apolipoprotein E deficient (apoE Ϫ/Ϫ ) mice were treated with a specific LTB4 receptor antagonist, CP-105,696, for 35 days. In apoE Ϫ/Ϫ mice, treatment with the LTB4 antagonist did not affect plasma lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(154 citation statements)
references
References 35 publications
(35 reference statements)
9
144
1
Order By: Relevance
“…A 5-LO promoter variant is associated with abnormal carotid artery intima-media thickness and heightened inflammatory biomarkers 30 . In addition, antagonists of LTB4 block the development of atherosclerosis in apo-E-deficient and LDRLdeficient mice 31 , and a congenic mouse strain with a heterozygous deficiency of 5-LO shows resistance to atherosclerosis 16 , further supporting the idea that greater activity of the 5-LO pathway has a role in predisposition to atherosclerosis.…”
Section: Discussionmentioning
confidence: 88%
“…A 5-LO promoter variant is associated with abnormal carotid artery intima-media thickness and heightened inflammatory biomarkers 30 . In addition, antagonists of LTB4 block the development of atherosclerosis in apo-E-deficient and LDRLdeficient mice 31 , and a congenic mouse strain with a heterozygous deficiency of 5-LO shows resistance to atherosclerosis 16 , further supporting the idea that greater activity of the 5-LO pathway has a role in predisposition to atherosclerosis.…”
Section: Discussionmentioning
confidence: 88%
“…For example, we demonstrated that deficiency of the gene encoding 5-lipoxygenase (Alox5) in mice protects against the development of aortic lesions [3,4], and that promoter variants of the human ALOX5 gene are associated with increased carotid intima-media thickness [5]. Other groups have also reported findings that support the involvement of the 5-LO/LT pathway in CVD traits [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 88%
“…2 The potential involvement of leukotrienes in the different stages of the atherosclerosis process eventually leading to cerebral and myocardial ischemia. Abbreviations: SMC smooth muscle cells, MMP matrix metalloproteinase, I/R ischemia and reperfusion protein E (ApoE) knockout mice in which either genetic or pharmacological targeting of the BLT 1 receptor reduces lipid accumulation and foam cell infiltration [36][37][38].…”
Section: Lipid Retention and Modificationmentioning
confidence: 99%
“…2) [10]. The chemoattractant activity induced by LTB 4 through BLT 1 and BLT 2 receptors expressed on monocytes may play an important role in the continued accumulation of macrophages at the site of the initial foam cell infiltration [36]. Since macrophages represent a major source of 5-LO in the cardiovascular system, LTB 4 -induced monocyte recruitment could potentially further exacerbate the inflammatory activity at sites of atherosclerotic lesions.…”
Section: Atherosclerotic Plaque Formationmentioning
confidence: 99%